5. Reflections on the Israeli-Palestinian Conflict - Avi Shlaim (For Palestine: Essays from the Tom Hurndall Memorial Lecture Group, 2023)
In this chapter I argue that the state of Israel is legitimate, but only within its original boundaries and that the Palestinians are the main victims of the conflict, victims of Israeli colonialism. The history of the region over the last sixty years can be convincingly explained in terms of the strategy of the ‘iron wall’, first expounded by Jabotinsky, which advocates negotiation only from a position of unassailable strength. The basic deal of ‘land for peace’ expressed in UN Resolution 242 was sound, but never effectively implemented and Rabin, the only Israeli prime minister prepared to negotiate, was murdered. The recent, brutal onslaughts on Gaza give little grounds for optimism.